2018
DOI: 10.3892/mmr.2018.9526
|View full text |Cite
|
Sign up to set email alerts
|

Profiling cytochrome P450 family 4 gene expression in human hepatocellular carcinoma

Abstract: Cytochrome P450 family 4 (CYP4) enzymes are known as microsomal omega (ω)-hydroxylases that metabolize fatty acids, eicosanoids, vitamin D and carcinogens. Thus, CYP4 enzymes may influence tumor development and progression. The aim of the present study was to evaluate the CYP4 expression profile in hepatocellular carcinoma (HCC) and its clinical relevance. The present study obtained CYP4 mRNA expression data for 377 HCC cases from The Cancer Genome Atlas cohort and performed Kaplan-Meier survival, Gene Ontolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…29,30 Previous findings indicate hepatocellular carcinoma (HCC) patients with good OS overexpress CYP4F12. 31 Although CYP4F12 was not altered in HNSCC, the protective role of CYP4F12 was similar to that found in HCC. SRD5A2 encodes steroid 5-α-reductase 2 that converts testosterone to the more potent androgen receptor agonist dihydrotestosterone.…”
Section: Discussionmentioning
confidence: 52%
“…29,30 Previous findings indicate hepatocellular carcinoma (HCC) patients with good OS overexpress CYP4F12. 31 Although CYP4F12 was not altered in HNSCC, the protective role of CYP4F12 was similar to that found in HCC. SRD5A2 encodes steroid 5-α-reductase 2 that converts testosterone to the more potent androgen receptor agonist dihydrotestosterone.…”
Section: Discussionmentioning
confidence: 52%
“…To the best of our knowledge, this is the first study that revealed the putative protective role of CYP3A7 in the prognosis of ccRCC. Members of the cytochrome P450 superfamily are a group of metalloproteins that involve in metabolic biotransformation of endogenous and exogenous substrates, including carcinogens [ 28 ]. Conversely, overexpression of CYP3A7 was witnessed in hepatocellular carcinoma [ 29 , 30 ], suggesting that it might exert varied functions among different types or stages of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome P450 (CYP450), belonging to ω-hydroxylase, participates in the metabolism of many endogenous substances and exogenous compounds, including fatty acids, docosahexenoic acid, and vitamin D, and of a wide variety of carcinogens and anticancer drugs [10,11]. These reactive metabolites would interact with DNA, thereby causing altered gene expression or function, and eventually carcinogenesis [12].…”
Section: Introductionmentioning
confidence: 99%